Most of the pelvic floor muscle functions in women differ in different body positions, yet others remain similar: systematic review with meta-analysis - Huang, Lu; Zhang, Zhi-Yuan; Liu, Hong; Gao, Min; Wang, Xiao-Qi; Duan, Xiao-Qin; Liu, Zhong-Liang (Frontiers in Medicine, 2023)
Objectives This systematic literature review and meta-analysis aimed to determine the effect of body position on the measurement of pelvic floor muscle (PFM) contractility and to analyze the influential factors. Data sources Five databases (PubMed, Web of Science, EMBASE, Cochrane Library and Scopus) were searched for relevant studies published up to 12nd October 2023. Study selection or eligibility criteria Included cross-sectional studies had to involve the assessment of pelvic floor muscle function in at least two positions. Study appraisal and synthesis methods We calculated standardized mean difference (SMD) with 95% confidence intervals (CI) to ascertain the potential effect of body position on outcomes. Results In total, we included 11 cross-sectional studies to ascertain the potential effect of body position on outcomes. There was no statistical difference in the results of maximum voluntary contraction (MVC) of the pelvic floor muscles when assessed in between supine and standing positions (SMD −0.22; 95% CI −0.72 to 0.28; p = 0.38). The results of the meta-analysis showed significantly larger values of resting voluntary contractions (RVC) measured in the standing position compared to the supine position (SMD −1.76; 95% CI −2.55 to −0.97; p < 0.001). Moreover, pelvic floor muscle movement during pelvic floor muscle contraction in the standing position was significantly better than that measured in the supine position (SMD −0.47; 95% CI −0.73 to 0.20; P < 0.001). Conclusion The results of this study showed that the RVC and PFM movement varied with the position of the assessment. In contrast, MVC values are independent of the assessment position and can be selected according to clinical needs. Systematic review registration PROSPERO, identifier CRD42022363734, https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022363734.